LA JUSTICIA RESTAURATIVA EN EL SISTEMA PENAL JUVENIL: LAS EXPERIENCIAS DE BRASIL Y CHILE (Revista Direito em Debate, 2020)
Restorative justice enables a new look at the pacification of conflicts and the harmonization of social relations. To this end, the present study aims to analyze how the process of implementation of the Restorative Juvenile Justice practices in Brazil and Chile occurs and how the public policies and juvenile criminal justice system of each country facilitates and/or hinders this process. To achieve this goal, the following questions are asked: what are the social, political and economic processes that facilitate and/or hinder the implementation of juvenile restorative justice practices in Brazil and Chile as public policies that are part of the justice system? The study, developed through a deductive approach method and the documentary and bibliographic search as a research technique, is structured in three moments: in the first, it outlines a panorama of juvenile restorative justice in Brazil, in the second moment, brings to discussion the reality of Juvenile restorative justice in Chile and, in the third subchapter, makes some comparative considerations between the two models. The findings show how each country implements juvenile restorative justice programs under close but different legal scenarios. Even though Brazil and Chile have, to a certain extent, solid legal systems and legal institutions, the application of Restorative Justice must be conceived and analyzed as a possibility of modernizing understanding and ways of dealing with conflicts.
Keywords: Brazil; Chile; juvenile penal system; Restorative Justice.